Briefing improves the management of a difficult mask ventilation in infants : Simulator study using Web-based decision support - St. Pierre, Michael; Breuer, Georg; Strembski, D.; Schmitt, Christopher; Lütcke, Björn (Anaesthesist, 2016)
Unanticipated airway problems in infants can rapidly develop into severe hypoxemia. Team members can provide support and suggest steps of action if a shared mental model of the next steps exists. Briefing prior to induction of anaesthesia may create such a shared mental model among all team members.The aim of the study was to assess whether a short briefing on the recommendations for an unexpected difficult airway, developed by the Working Group on Paediatric Anaesthesia of the German Society for Anaesthesiology and Intensive Care Medicine, would influence the management of an unexpected difficult mask ventilation in an infant. The study also aims to assess whether a shared mental model would encourage the anaesthesia nurse to speak up and foster implicit coordination.Nineteen teams consisting of an anaesthesia resident and an anaesthesia nurse participated in a scenario of an urgent induction of anaesthesia in an infant. Teams were randomized to either conduct a briefing on the recommendations for an unexpected difficult airway prior to induction of anaesthesia or to have access to a Web-based cognitive aid with an emergency manual page containing the identical algorithm if needed. Induction of anaesthesia triggered upper airway obstruction and desaturation. The time course of desaturation followed published physiologic modelling. The time until the obstruction was relieved was recorded. Video recordings of the scenarios were analysed with respect to coordination patterns prior to induction as well as to coordination forms (implicit vs. explicit) during the emergency. At the end of the course, participants were asked to fill out a questionnaire.Teams of both groups checked on the availability of airway equipment, but teams in the briefing group talked more often about treatment steps to relieve airway obstruction (p < 0.005). The time until the obstruction was relieved was significantly shorter in the briefing group (median: 80 s vs. 126 s; p < 0.005). In 45 % of the intervention scenarios the nurse suggested the solution to the airway problem whereas only 10 % of the nurses in the control group proposed a measure to relieve the obstruction (n.s.). Both groups showed no difference in the frequency of implicit vs. explicit coordination patterns. Nurses from the intervention group found the situation to be less an emergency and felt better prepared than nurses from the control group (p < 0.05).Briefings prior to anaesthesia induction in paediatric anaesthesia should include management of unanticipated problems. In a simulation setting, a briefing on treatment steps for an unexpected difficult airway improves management of an upper airway obstruction. Explicit communication of intended actions by the anaesthesiologist may foster speaking up by team members.
EVALuna2:16725